Changing Mechanisms of Enterprise Security (Comparing Beyond Corp with Prevalent Network Security Mechanisms) - Amutha, B; Saxena, Swasti; Das, Abhinaba (International Journal of Engineering and Technology, 2018)
War driving, camp out etc. are common methodologies of gaining access of a company’s network and resources illegally. Packet capturing, out of thin air, brute force etc. are common mechanisms to gain key or password access to any company’s applications. In the times where hacking and cyber-attacks have become prevalent, companies are deploying various network security mechanisms to counter these attacks and to safe guard company’s applications and data. Beyond Corp is a new technology that is being used by Google these days to safe guard its applications. In this paper we will compare some of the network security mechanisms that many companies use to avoid cyber-attacks with Beyond Corp technology which is being used by Google to avoid security breach in the company’s network and applications.